إيقاع المهن في شعر أبي تمام (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
عرف الإنسان الإيقاع جسداً وصوتاً وتفكيراً، وسعى جهده في سبيل تحقيق التوازن والانسجام بين الإيقاع الصادر عنه والإيقاع الذي تنتجه البيئة، ولمّا كان الشاعر ابن بيئته، يؤثّر فيها ويتأثّر بها عمدنا إلى دراسة إيقاع المهن في شعر أبي تمام، فألقينا الضوء على أهم المنعطفات في حياته، ما تعلق بطبيعة البيئة التي عاش فيها أو انتقل إليها، أو ما تعلق بطبيعة المهنة التي تكسّب منها. نستعين بالمنهج الاجتماعي، فنكشف عن التناسب الحاصل بين الإيقاع في شعر أبي تمام وإيقاع الحياة في العصر العباسي، ثم نلجأ إلى المنهج البنيوي، لإظهار مدى التوازن في العلاقة بين إيقاع المهنة التي امتهنها أبو تمام وإيقاع الصور والتراكيب في شعره. وبموجب ذلك نستطيع اكتشاف أهم مقومات الإبداع في فنه على مستويي الموسيقا ( الداخلية والخارجية ) من ناحية، وعلى مستوى البنية بالنظر إلى علاقة المفردات فيما بينها من ناحية ثانية. Man knew rhythm as thought, sound and flesh. He did his best to achieve balance and harmony between the rhythm that came from him and the one that the environment produced. Because the poet is the son of his environment, he is affected in it and influenced by it. In the paper, we study the rhythm of professions in the poetry of Abe Tammam, casting light on the most important turning points in his life, either those which were related to the nature of the environment that he lived in or moved to, or those which were connected by the nature of the profession that he earned money from. The social method helps us to reveal the agreement that happens between the rhythm in the poetry of Abe Tammam and the rhythm of life in the Abbasi age. Then we resort to the structural method to show the range of coincidence and the balance between the rhythm of the profession which Abe Tammam professed, and the rhythm of figures and structures in his poetry.